(untitled) (Agricultural Engineering, 2020)
It is justified that the problems related to changes in physico-chemical properties, concentration of trace elements in lubricat-ing oil and the impact of these changes and their dynamics on vehicle structural elements should be considered in detail. It is important that empirical data, theoretical relationships and test results should be taken into account. The paper presents re-search results of the selected physico-chemical parameters and the content of metals in samples of the used engine oil. The samples were collected both after the fuel system failure and during the operation of the farm tractor according to the date of changing engine oil assumed by the producer. An instrumental chemical analysis method HDXRF was used to determine chang-es of the content of trace elements Fe, Sn, Cu, Pb, P, Zn, Ca in engine oil. Additionally, changes in physico-chemical properties were determined with the use of FT-IR spectrometry. Courses of these changes were analysed on account of their impact on the utility properties of the engine oil.